PERENCANAAN PENGEMBANGAN DANAU SEPER BEBASIS ANALISIS SOAR DI DESA WISATA RINTISAN LEMBEAN KABUPATEN MINAHASA UTARA - Ruslani, Ruslani; Wijanarko, Sony; Lagarense, Bet El Silisna; Tangkau, Kezia Waya (Jurnal Ilmu Pariwisata, 2025)
This study aims to formulate a strategic development plan for Lake Seper as a locally-based tourist destination in Lembean Pilot Tourism Village, North Minahasa Regency, using the SOAR (Strengths, Opportunities, Aspirations, Results) analysis framework. This appreciative and forward-looking approach is employed to identify and integrate internal strengths and community aspirations with external opportunities and expected outcomes in a participatory manner. Data were collected through direct field observations, in-depth interviews with key local stakeholders (village officials, community leaders, and tourism actors), and document analysis of existing development plans and policy frameworks. The findings reveal that Lake Seper possesses significant natural and cultural assets, underpinned by strong community engagement in resource management and conservation. The development strategy focuses on multi-stakeholder collaboration, infrastructure enhancement, and community empowerment through capacity-building programs. The implementation of this strategy is expected to increase tourist arrivals, stimulate local economic growth, and promote the preservation of cultural heritage and environmental sustainability in alignment with ecological balance.